2021
DOI: 10.21203/rs.3.rs-93878/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social and emotional loneliness among college students during the COVID-19 pandemic: the predictive role of coping behaviours, social support, and personal resilience

Abstract: ObjectiveTo determine the influence of coping behaviors, resilience, and social support on students' emotional and social loneliness during the COVID‐19 pandemic.Design and MethodsA cross‐sectional research design was used to gather data from 303 college students from the Central Philippines using four standardized scales through an online survey.FindingsLoneliness among students was high during the coronavirus pandemic. Resilience, coping behaviors, and social support were identified as protective factors aga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
2
25
1
Order By: Relevance
“…The result of the first hypothesis is consistent, to some extent, with the study conducted by Al-Fiqi & Aboel-Fetouh (2020) which showed that students had suffered from loneliness moderately. This result is different from the result of the study carried out by Labrague et al, (2020), which revealed a high level of loneliness among the students during the COVID-19 pandemic. Therefore, the researcher thinks that this difference might be attributed to the nature of the samples.…”
Section: B -Reliability Coefficientscontrasting
confidence: 99%
See 4 more Smart Citations
“…The result of the first hypothesis is consistent, to some extent, with the study conducted by Al-Fiqi & Aboel-Fetouh (2020) which showed that students had suffered from loneliness moderately. This result is different from the result of the study carried out by Labrague et al, (2020), which revealed a high level of loneliness among the students during the COVID-19 pandemic. Therefore, the researcher thinks that this difference might be attributed to the nature of the samples.…”
Section: B -Reliability Coefficientscontrasting
confidence: 99%
“…The current research is consistent with previous studies such as Wilczewski et al, (2021), Labrague et al, (2020), and Al-Fiqi & Aboel-Fetouh (2020) which focused on loneliness among university students during the COVID-19 pandemic. The most significant characteristic of this research is its difference in terms of the sample because the previous studies' samples were from Poland, Swiss, the Philippines, and Egypt.…”
Section: Comment On Previous Studiessupporting
confidence: 92%
See 3 more Smart Citations